2011
DOI: 10.1073/pnas.1012807108
|View full text |Cite
|
Sign up to set email alerts
|

Strong evidence for terrestrial support of zooplankton in small lakes based on stable isotopes of carbon, nitrogen, and hydrogen

Abstract: Cross-ecosystem subsidies to food webs can alter metabolic balances in the receiving (subsidized) system and free the food web, or particular consumers, from the energetic constraints of local primary production. Although cross-ecosystem subsidies between terrestrial and aquatic systems have been well recognized for benthic organisms in streams, rivers, and the littoral zones of lakes, terrestrial subsidies to pelagic consumers are more difficult to demonstrate and remain controversial. Here, we adopt a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
329
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(350 citation statements)
references
References 66 publications
16
329
3
2
Order By: Relevance
“…In this study, we found that intraspecific variation stemming from local adaptation is sufficient to drive similar patterns. For example, pelagic crustaceans, such as calanoid copepods, have been shown to rely heavily on terrestrial material in oligotrophic lakes [40] and are also a common prey for sticklebacks [28]. We observed that mesocosms containing litter from the most productive cottonwood genotypes fostered a greater abundance of calanoid copepods, which ultimately led to a larger decrease in calanoid abundance when fish were present ( figure 3).…”
Section: Discussionmentioning
confidence: 75%
“…In this study, we found that intraspecific variation stemming from local adaptation is sufficient to drive similar patterns. For example, pelagic crustaceans, such as calanoid copepods, have been shown to rely heavily on terrestrial material in oligotrophic lakes [40] and are also a common prey for sticklebacks [28]. We observed that mesocosms containing litter from the most productive cottonwood genotypes fostered a greater abundance of calanoid copepods, which ultimately led to a larger decrease in calanoid abundance when fish were present ( figure 3).…”
Section: Discussionmentioning
confidence: 75%
“…The OM sources sampled were selected based on the feeding modes of the primary consumers selected (zooplankton and Corbicula fluminea): phytoplankton (freshwater, estuarine and marine), macroalgae, microphytobenthos (MPB), sediment organic matter (SOM), particulate organic matter (POM), and vascular plants (terrestrial and aquatic; Cole et al 2011, Dias et al 2014.…”
Section: Field Samplingmentioning
confidence: 99%
“…Alternatively, other theories such as the Flood Pulse Concept (FPC) of Junk et al (1989) suggest that the movement of terrestrial resources from the floodplain and catchments during flooding and rainfall events may be a significant source of energy to aquatic systems. More recently, paradigms about autochthonous carbon dominating lakes are being questioned (Cole et al 2011). The significance of allochthonous DOC to aquatic ecosystems is being further recognised with the understanding that terrestrial subsidies are playing a much greater role in some systems than previously thought (Tanentzap et al 2014).…”
Section: Introduction To Special Issuementioning
confidence: 99%